The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2001
DOI: 10.1111/j.1745-6584.2001.tb02336.x
|View full text |Cite
|
Sign up to set email alerts
|

Trace Metal Concentrations in Shallow Ground Water

Abstract: Trace metal clean sampling and analysis techniques were used to examine the temporal patterns of Hg, Cu, and Zn concentrations in shallow ground water, and the relationships between metal concentrations in ground water and in a hydrologically connected river. Hg, Cu, and Zn concentrations in ground water ranged from 0.07 to 4.6 ng L-1, 0.07 to 3.10 micrograms L-1, and 0.17 to 2.18 micrograms L-1, respectively. There was no apparent seasonal pattern in any of the metal concentrations. Filtrable Hg, Cu, and Zn c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2002
2002
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 24 publications
2
5
0
Order By: Relevance
“…These results indicate minimum seasonal variability of data. The lack of a seasonal pattern in heavy metal concentrations in other aquifers has also been noted in previous studies (Zelewski et al 2001).…”
Section: Data Preparationsupporting
confidence: 83%
See 1 more Smart Citation
“…These results indicate minimum seasonal variability of data. The lack of a seasonal pattern in heavy metal concentrations in other aquifers has also been noted in previous studies (Zelewski et al 2001).…”
Section: Data Preparationsupporting
confidence: 83%
“…Although data for heavy metals are available from 1975 through 2000, >95% of the samples are in the period between 1989 and 2000. Unreliability of heavy metal data collected prior to 1990 across the United States has been well studied and explained by Zelewski et al (2001). The major reason for this conclusion is the lack of adherence to clean sampling techniques prior to 1990.…”
Section: Data Preparationmentioning
confidence: 99%
“…These transition zones react very sensitive due to a change of geochemical conditions, which can effect a remobilization of trace elements with a risk for surface water and groundwater contamination (e.g. Balistrieri et al 1994;Caetano et al 2003;Kelly et al 2005;Selim and Sparks 2001;Zelewski et al 2001).…”
Section: Introductionmentioning
confidence: 98%
“…Moreover, groundwater sampling normally takes only 10 -15 min, during which any contamination of the water sample by released metal ions is probably very small with respect to the groundwater composition; in addition the sampler is flushed, as it is lowered open, to the sampling depth. Trace metal clean sampling and analysis techniques are described in detail in Zelewski et al (2001). Given these guidelines and the low concentrations recorded by the test, it is concluded that despite some metal release, these concentrations are insignificant compared with the observed concentrations in the groundwater.…”
Section: Methodsmentioning
confidence: 98%